GROWTH RATES OF YOUNG BUNI Barbus sharpeyi (GUNTHER,1874) AND COMMON CARP Cyprinus carpio L. UNDER LABORATORY CONDITIONS - Al-Hamadany, Qusay Hamid (Iraqi Journal of Aquaculture, 2022)
Fishes of buni ,(Barbus sharpeyi (Gunther,1874)) with average weight (20.13 ± 1.77) gm and common carp ,(Cyprinus carpio) with average weight (20.63 ± 0.56) gm were reared in eight plastic aquariums of 15 L cabacity. Four treatments (two replicates) were carried out as following:(1) 10 common carp per aquarium, (2) 8 buni and 8 common carp in one aquaria, (3) 6 buni and 6 common carp in another aquarium and (4) 10 buni per aquarium. Artificial food (29.31 % protein) was fed to the fishes once daily 3 % of body weight.Water temperature was 26-28ºC, Oxygen concentration 6.2 mg/L and pH 8.1. Results showed no significant (P>0.05) differences between buni in 2 ,3 ,4 treatments, however fish in treatments 4 (0.059 gm) mean growth rate showed better growth than of fish in both 2 , 3 (0.053 , 0.056gm). The experiment showed highest growth parameters of common carp compared with buni .This may be due to its efficiency in utilization of food comparing to buni, which showed lower growth parameters. More experiments are needed, using different types of diets to achieve better growth of buni .